2008
DOI: 10.1016/j.jallcom.2007.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy characterization of laser welding cast Ni-based superalloy K418 turbo disk and alloy steel 42CrMo shaft

Abstract: Microstructure characterization is important for controlling the quality of laser welding. In the present work, a detailed microstructure characterization by transmission electron microscopy was carried out on the laser welding cast Ni-based superalloy K418 turbo disk and alloy steel 42CrMo shaft and an unambiguous identification of phases in the weldment was accomplished. It was found that there are ␥-FeCrNiC austenite solid solution dendrites as the matrix, (Nb, Ti) C type MC carbides, fine and dispersed Ni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the joining of dissimilar alloys, laser welding method provides some advantages such as high energy density, rapid heating/cooling velocity and accessibility to the heating zone [20,21]. Specially, the laser welding-brazing method to attach metallurgical non-fitting partners to each other can suppress effectively the growth of brittle intermetallic compounds [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In the joining of dissimilar alloys, laser welding method provides some advantages such as high energy density, rapid heating/cooling velocity and accessibility to the heating zone [20,21]. Specially, the laser welding-brazing method to attach metallurgical non-fitting partners to each other can suppress effectively the growth of brittle intermetallic compounds [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Fathy et al [6] reported that liquid to solid volume ratio should be kept higher than 5:1 to successfully fabricate Babbitt-steel bimetallic composite at low pouring temperature with the assistance of Sn-Pb interlayer. Similarly, Liu et al [26] found that the effective interfacial bonding could be achieved using a liquid-to-solid volume ratio of 8:1 that mainly depends on the imported heat energy of the poured liquid metal. One of the previous investigations [4] is in good agreement with the above findings that the liquid-to-solid volume ratios of 5:1 and 6.5:1 are not enough to partially remelt the tin + tin oxide layer (that formed during atmosphere preheating) on the surface of tinned solid steel, resulting in the appearance of an unboned interface area.…”
Section: Effect Of Volume Ratio Of Liquid-to-solid On the Interfacialmentioning
confidence: 95%
“…The substrates and coating materials used in this experiment were of AISI 4130 steel and Stellite 6, respectively; the chemical compositions of the two materials are shown in Table 1. AISI 4130 steel is one type of high-strength low-alloy steel [29], commonly used in the manufacture of crankshafts for power plant [14], for automotive application [15], shaft of turbocharger [16], and aircraft components [17]. Round bar of AISI 4130 steel, with a diameter of 5.5 mm, was laser clad with Stellite 6 powder with the powder size range of 45-150 lm.…”
Section: Laser Cladding and Microstructural Examinationmentioning
confidence: 99%